An Integrated Care Model With Implementation Roadmap to Improve Chlamydia trachomatis Management and Control in India - Thomas, Pierre P. M.; Allam, Ramesh R.; Ambrosino, Elena; Malogajski, Jelena; Lal, Jonathan A.; Morré, Servaas A.; Peters, Remco P. H. (Frontiers in Public Health, 2018)
Chlamydia trachomatis is the world´s most prevalent bacterial Sexually Transmitted infection (STI). It is associated with a wide range of health consequences and sequelae in the short and in the long term. Enhanced control of C. trachomatis infection is warranted particularly in low and middle income countries such as India, where most of the burden goes unnoticed and where no systematic data is available to gauge the current situation. The World Health Organization (WHO) recently issued its latest strategy on STIs, which is aligned with the achievement of the Sustainable Development Goals (SDGs). Taking the WHO framework into account; this paper puts forward an integrated care model to strengthen the management and control of C. trachomatis in India. The model is compiled of five key components of STI management (awareness, prevention diagnosis, treatment and follow-up). The model also takes barriers to effective C. trachomatis control into account. The barriers are discussed and compiled into different categories. A roadmap for the implementation of models such as this one to enhance Chlamydia trachomatis control in the future is provided.